Knowing and interpreting prekindergarten policy: A Bakhtinian analysis - Wilinski, Bethany (Education Policy Analysis Archives, 2017)
Many state-funded prekindergarten (preK) programs are implemented through school-community partnerships, which has been promoted as a way to increase preK access, to meet the needs of families, and to ensure program quality (Schumacher, Ewen, Hart, & Lombardi, 2005). In spite of the potential benefits of such partnerships, there are also challenges to bringing together the K-12 and ECE systems (McCabe & Sipple, 2011). In this paper I use Bakhtin’s (1981) notions of authoritative and internally persuasive discourse to analyze the discourse that staff members at a Lakeville, Wisconsin, ECE partner site used to situate their approach to assessment in opposition to state and district assessment policy. ECE partner site staff drew on their institution’s long history and strong sense of best practice in early education to characterize required preK assessments as unnecessary, too aligned with the elementary grades, and a duplication of other approaches to assessment that they valued. Yet, even as they resisted the assessments, ECE partners’ internally persuasive discourse shifted slightly over time; staff members conceded that some aspects of the assessment policy had a positive effect on their program. This discursive analysis provides insight into some of the challenges associated with bringing together the ECE and K-12 systems. It points to the need for policy to address the particular challenges faced by ECE partners as they encounter new mandates in public preK and for the need to ensure that partnerships are characterized by mutual understanding.